Intelligence in Countering Hoaxes in Indonesia - Nainggolan, Daniel Junwaldi MP (Faculty of Law Universitas Negeri Semarang, 2022)
This research is motivated by the existence of many potential people who are consumed by hoax information that is available on various social media that are freely circulating in cyberspace. The potential for spreading hoax information in the Salatiga area is very disturbing to the community so that appropriate efforts are needed to overcome these problems. The purpose of this study is to explain the function of gathering intelligence in preventing the spread of hoaxes ahead of the presidential election in the jurisdiction of the Salatiga Police, the mechanism for raising intelligence and explaining the factors that influence it. The knife of analysis in this research is the theory of strategic management, management theory and the concept of raising intelligence. This research was conducted with a qualitative approach with a case study research method, which was then carried out through interviews, observations and document studies and analyzed by reducing data, presenting data and verifying data. The results of this study indicate the function of gathering intelligence in preventing the spread of hoaxes ahead of the presidential election in the jurisdiction of the Salatiga Police. The intelligence-raising mechanism is implemented with planning steps, the implementation of which includes the stages of infiltration, dispersal, denial, direction, investigation of allegiances, shifts, and mergers, as well as evaluating and reporting intelligence-raising actions to the leadership. The influencing factors come from the action agents/intruders who do not have reliable capabilities evenly in the implementation of intelligence-raising actions, the limited budget for intelligence-raising operations, the lack of infrastructure facilities used for intelligence-raising operations and the lack of appropriate methods in implementing the action-raising activities. intelligence, as well as the sensitivity of the target to the actions of infiltrating agents who carry out these intelligence-raising actions. Suggestions in this study are to provide intruders with various intelligence-raising action training standards, and provide intruders with various abilities to approach the public and the ability to utilize technology that can be used for intelligence-raising actions.